Lossy/Lossless Floating/Grounded Inductance Simulation Using One DDCC - M. A. Ibrahim; S. Minaei; E. Yuce; N. Herencsar; J. Koton (Radioengineering, 2012)
In this work, we present new topologies for realizing one lossless grounded inductor and two floating, one lossless and one lossy, inductors employing a single differential difference current conveyor (DDCC) and a minimum number of passive components, two resistors, and one grounded capacitor. The floating inductors are based on ordinary dual-output differential difference current conveyor (DO-DDCC) while the grounded lossless inductor is based one a modified dual-output differential difference current conveyor (MDO-DDCC). The proposed lossless floating inductor is obtained from the lossy one by employing a negative impedance converter (NIC). The non-ideality effects of the active element on the simulated inductors are investigated. To demonstrate the performance of the proposed grounded inductance simulator as an example, it is used to construct a parallel resonant circuit. SPICE simulation results are given to confirm the theoretical analysis.